تقييم الأداء المالي عن طريق تحليل المردوديةةالاقتصادية - منى, زاوي; سندس فاطمة الزهراء, خلادي; رشيدة, بوعروة; نور الايمان, بركة (جامعة الوادي - University of Eloued, 2023)
": الملخص: تهدف هذه الدراسة إلى تقييم األداء المالي للمؤسسة الاقتصادية وذلك تحليل المردودية بنا ءا على القوائم المالية للمؤسسة والمتمثلة في الميزانية المحاسبية وجدول حسابات النتائج لتشخيص الوضعية المالية الحقيقة للمؤسسة بالاعتماد على الميزانية الاقتصادية وتحليل المردودية الاقتصادية والمالية ومعرفة مدى مساهمة الاستدامة في الأموال الخاصة وصولا إلي أثر الرافعة المالية لمعرفة أهمية الدراسة قمنا بتطبيق هذه الأدوات المالية على المؤسسة الوطنية لتوزيع الكهرباء والغاز سونلغاز فرع الوادي وقد توصلت هذه الدراسة إلى عدة نتائج أهمها أن المؤسسة في وضعية مالية متدهورة في هذه الفترة نظرا لمواجهة وباء التي كانت أزمة اقتصادية عالمية ذات أثر واضح على المردودية الاقتصادية للمؤسسة فكانت بنسبة ضئيلة جدا مقارنة بالفوائد المفروضة على الاستدانة الواضحة على أثر الرافعة المالية للمؤسسة ,أيضا تقييم الأداء المالي له دور كبير في تحليل وقياس الأعمال المنجزة في فترة زمنية والذي يهدف إلى كشف نقاط الضعف والقوة والعمل على معالجتها و توفير البيانات التي تقودنا الي اتخاذ القرارات الصائبة والفعالة في المضي قدمنا نحو آفاق اقتصادية رائد مستقبلا " "t: This study aims to divide the financial performance of the economic institution by analyzing the profitability based on the financial statements of the institution represented in the accounting budget and the table of accounts of the results to diagnose the real financial position of the institution based on the budget economy and the analysis of economic and financial profitability and knowing the extent of the contribution of borrowing to private funds to reach the impact leverage and to know the importance of the study, we applied these financial tools to the National Electricity and Gas distribution Corporation, Sonelgaz , Eloued branch .this study reached several results the most important of which are, the corporation is in a deteriorating financial situation during this period due to the wave of the epidemic, which was a globaeconomic crisis with a clear impact on economic profitability. It was a very small percentage compared to the benefits imposed on the institution. It is evident in the impact of financial leverage of the institution. Also, the evaluation of financial performance has a major role in analyzing and measuring the work carried out in a certain period of time, which aims to detect weaknesses and strengths and work to address them and provide data that leads us to make the right and effective decisions in Al-Ghani as far as pioneering economic prospects have developed, in the future. "
Keywords: الأداء المالي، تقييم الأداء المالي،تحليل المردودية ،القوائم المالية ،الميزانية المحاسبية ،الميزانية الاقتصادية، الأدوات المالية ،المردودية الاقتصادية والمالية، أثر الرافعة المالية; Key words: the financial performance, divide the financial performance, analyzing the profitability, the financial statements, the accounting budget, the budget economy, financial tools, economic and financial profitability, the impact leverageط